Estudio de factibilidad para la creación de un sitio web para la unidad educativa particular “Miguel Ángel Samaniego” de la parroquia la Unión. - Minda Napa, Jorge Antonio (2020)
The following case study tries to carry out a Feasibility study for the creation of a website for the Miguel Ángel Samaniego private educational unit of La Unión parish. The line of systems research that has been used is "Development of Information and Communication Systems" and the subline "Development of Computer Systems", currently educational institutions have implemented mostly websites which were seen in the need to implement them because the vast majority of businesses and institutions have at least one website that is like their cover letter, when conducting a feasibility analysis to find out how feasible it is to create a website can help reduce time in processes and inform users quickly and reliably in real time.